2016
DOI: 10.1146/annurev-anchem-071015-041742
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Optical Microcavity Resonators in Analytical Chemistry

Abstract: Optical resonator sensors are an emerging class of analytical technologies that use recirculating light confined within a microcavity to sensitively measure the surrounding environment. Bolstered by advances in microfabrication, these devices can be configured for a wide variety of chemical or biomolecular sensing applications. The review begins with a brief description of optical resonator sensor operation followed by discussions regarding sensor design, including different geometries, choices of material sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 153 publications
(180 reference statements)
1
55
0
Order By: Relevance
“…433,434 A refractive indexed based on a sensing modality using silicon oxide micro-ring resonators was used for detecting binding events on an array of 30 µm diameter silicon rings. The multi-channel chip described in 433 contained 32 rings, with the possibility of measuring each independently using a tunable near-IR laser to launch an optically guided mode.…”
Section: Application Of Nanodiscs In Functional Studies Of Membranmentioning
confidence: 99%
“…433,434 A refractive indexed based on a sensing modality using silicon oxide micro-ring resonators was used for detecting binding events on an array of 30 µm diameter silicon rings. The multi-channel chip described in 433 contained 32 rings, with the possibility of measuring each independently using a tunable near-IR laser to launch an optically guided mode.…”
Section: Application Of Nanodiscs In Functional Studies Of Membranmentioning
confidence: 99%
“…Optical read-out is undoubtedly a very fascinating solution among detection methods, as it allows remote sensing of the investigated parameters, being thus minimally invasive, while miniaturization enables testing with ultra-low quantities of materials, both important factors particularly in the fields of biological, biochemical and biomedical analyses [2]. Various types of sensors that respond to the mentioned requirements have been lately investigated, based on resonant micro-cavities [1,3,4], photonics crystals [5][6][7][8][9], ring resonators [10][11][12][13][14][15], or whispering gallery modes [16], just to cite a few of them. However, there is still the need of demonstrating the functionality of simple and low-cost devices to be used as core elements of micro-opto-fluidic sensors combined with suitable readout methods.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In addition, they can be utilized as highly sensitive detectors for chemical vapors and biosensors. [18][19][20][21][22] It has been observed that the storage of porous silicon films in ambient air causes uncontrolled oxidation. The silicon partially turns into silicon dioxide (SiO 2 ), and consequently the properties of porous silicon are changed.…”
Section: Introductionmentioning
confidence: 99%